Fuzzy linear programming with a-cut approach - Yeni Rokhayati (Fakulti Sains dan Teknologi, 2012)
Linear programming has been used to solve optimization problems in many industries. In most of the problems, the decision maker chooses to state the inequalities and coefficients that are used in objective function and constraints by vague expressions. Based on the fuzzy sets theory, fuzzy linear programming is developed to model and solve the problems.